Chaucer's gifts exchange and value in the Canterbury tales - Epstein, Robert 1964- (University of Wales Press, 2018)
Geoffrey Chaucer's Canterbury Tales, the most celebrated literary work of medieval England, portrays the culture of the late Middle Ages as a deeply commercial environment, replete with commodities and dominated by market relationships. However, the market is not the only mode of exchange in Chaucer's world or in his poem. Chaucer's Gifts reveals the gift economy at work in the tales. Applying important recent advances in anthropological gift theory, it illuminates and explains this network of exchanges and obligations. Chaucer's Gifts argues that the world of the Canterbury Tales harbours deep commitments to reciprocity and obligation which are at odds with a purely commercial culture, and demonstrates how the market and commercial relations are not natural, eternal, or inevitable - an essential lesson if we are to understand Chaucer's world or our own
Keywords: Chaucer, Geoffrey -- 1343-1400 -- The Canterbury tales; Handel -- Motiv; Geschenk -- Motiv; Tausch -- Motiv; Chaucer, Geoffrey / -1400 / Criticism and interpretation; Chaucer, Geoffrey / -1400 / Themes, motives; Chaucer, Geoffrey / -1400; Commerce in literature; Themes, motives; Criticism, interpretation, etc